Evaluation of Biochemical and Physiological Alterations Associated with Repeated Therapeutic Paracetamol Administration in Children: Impact on Hepatic Enzymes and Oxidative Stress Biomarkers - Shahid Ali, Zarka Sarwar, Jalil Khan, Rahat Jan Wazir, Roshaan Bashir, Abdul Samad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Paracetamol is one of the most commonly used antipyretic and analgesic drugs in children. It is safe in recommended therapeutic doses but may affect the metabolism and oxidative balance of the liver after repeated use over a few days. The liver is directly involved in the metabolism of paracetamol, and chronic and/or excessive consumption can affect the enzymes and antioxidant defense systems in the liver. Objective: To evaluate biochemical and physiological alterations associated with repeated therapeutic paracetamol administration in children, with special focus on hepatic enzymes and oxidative stress biomarkers. Methods: This descriptive analytical study was carried out in Pak International Medical College Peshawar for period of time January 2023 to June 2023. The children were collected by non-probability consecutive sampling method giving a total of 72 children aged 1–12 years who were taking the same therapeutic dose of Paracetamol for fever or pain. The children were split into three groups based on the number of days Paracetamol was taken: Group A (1-2 days of Paracetamol use), Group B (3-5 days of Paracetamol use) and Group C (>5 days of Paracetamol use). Demographic data, clinical details, paracetamol dosage, frequency, mode and duration of administration were noted. The assessment of physiological parameters, hepatic enzymes, renal function tests, hematological parameters and oxidative stress biomarkers were done. For data analysis SPSS version 25 was used and p value < 0.05 was considered statistically significant. Results: The mean age of the children was 5.8 ± 2.7 years. Out of 72 children, 40 (55.6%) were male and 32 (44.4%) were female. ALT and AST levels increased significantly with longer duration of paracetamol use. ALT increased from 28.6 ± 8.4 U/L in Group A to 46.7 ± 15.8 U/L in Group C, while AST increased from 31.2 ± 9.1 U/L to 52.3 ± 18.4 U/L. Malondialdehyde levels were also significantly higher in Group C, increasing from 2.4 ± 0.7 nmol/mL in Group A to 4.5 ± 1.2 nmol/mL in Group C. Antioxidant markers, including glutathione, superoxide dismutase, catalase, and total antioxidant capacity, showed a significant decline with longer duration of use. Raised ALT, raised AST, increased malondialdehyde, and reduced antioxidant capacity were more frequent among children receiving paracetamol for more than five days. Conclusion: Repeated therapeutic administration of paracetamol in children was associated with mild but significant alterations in hepatic enzymes and oxidative stress biomarkers, especially when used for more than five days. Although no severe hepatic dysfunction was observed, prolonged or frequent use should be avoided unless clinically indicated. Correct weight-based dosing, caregiver education, and monitoring in selected children with prolonged fever are recommended. Keywords: Paracetamol, children, hepatic enzymes, ALT, AST, oxidative stress, malondialdehyde, glutathione, antioxidant capacity.